Updated understanding of Staphylococcus aureus in atopic dermatitis: From virulence factors to commensals and clonal complexes. Issue 10 (30th July 2021) - Hwang, Jonwei; Thompson, Alyssa; Jaros, Joanna; Blackcloud, Paul; Hsiao, Jennifer; Shi, Vivian Y.
Abstract: Atopic dermatitis (AD) is a common inflammatory dermatosis that has multiple contributing factors including genetic, immunologic and environmental. Staphylococcus aureus (SA) has long been associated with exacerbation of AD. SA produces many virulence factors that interact with the human skin and immune system. These superantigens and toxins have been shown to contribute to adhesion, inflammation and skin barrier destruction. Recent advances in genome sequencing techniques have led to a broadened understanding of the multiple ways SA interacts with the cutaneous environment in AD hosts. For example, temporal shifts in the microbiome, specifically in clonal complexes of SA, have been identified during AD flares and remission. Herein, we review mechanisms of interaction between the cutaneous microbiome and SA and highlight known differences in SA clonal complexes that contribute to AD pathogenesis. Detailed knowledge of the genetic strains of SA and cutaneous dysbiosis is becoming increasingly relevant in paving the way for microbiome‐modulating and precision therapies for AD. Abstract : Staphylococcus aureus is a known contributor in the pathogenesis of atopic dermatitis. This review evaluates and presents literature on recent developments in this field; mainly interactions between S. aureus and the cutaneous microbiome and immune milieu, including antimicrobial peptides (AMPs), phenol soluble modulins (PSMs), and other mechanisms through which commensals inhibit S. aureus growth and virulence. Known differences between S. aureus clonal complexes and recently emerging treatments targeting S. aureus in atopic dermatitis are also highlighted.